Women making art: history, subjectivity, aesthetics - Meskimmon, Marsha.. (Routledge, 2003)
Women have been making art for centuries, yet their work has been seen as secondary or has gone unrecognized altogether. "Women making art" asks why this is so, and what it would take for us to realize the extent of women's extraordinary contribution to the arts. Marsha Meskimmon mobilizes contemporary feminist thinking to reconsider how and why women have made art. She examines work by a wide range of women artists fomr different cultures and historical periods, including Rebecca Horn, Rachel Whiteread, Shirin Neshat and Maya Lin, emphasizing the diversity of women's arts and the importance of differences between women.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques